Fearing Tax Rise Will Cost Jobs, Tobacco Workers Plan A Protest (Tufts Archival Research Center, 2007)
Article from a 1994 New York Times newspaper reporting Philip Morris' plans to shut down its Richmond plant for one day, allowing its workers to protest a proposed cigarette tax increase in Washington. Notes the protest organized by the Tobacco Action Committee will involve tobacco workers from across the country. Mentions Senator Edward Kennedy's inquiries on nicotine additives that make cigarettes addictive.